2016
DOI: 10.1159/000447819
|View full text |Cite
|
Sign up to set email alerts
|

MiR-139-5p is Increased in the Peripheral Blood of Patients with Prostate Cancer

Abstract: Background: Emerging evidence suggested that microRNAs (miRNAs) play a causal role in cancer tumorigenesis. Aberrant expression of miRNA (miR)-139-5p has been observed in various types of cancers. The present study evaluated the relationship between miR-139-5p expression levels and prostate cancer (PCa), to assess the feasibility of using peripheral blood miR-139-5p as a potential non-invasive biomarker for PCa. Methods: Total RNA was extracted from peripheral whole blood samples from 45 PCa patients, 45 benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
(12 reference statements)
1
18
0
Order By: Relevance
“…It has been previously shown that PVT1 was highly expressed in HCC compared with non-tumor tissues, and its overexpression predicts recurrence by our group and other groups [21]. We had also surveyed the genetic regulatory network of PVT1 in HCC through a gene microarray and RNAsequecing data mining with bioinformatics method to investigate the potential mechanism of PVT1 in HCC, and found that DLC1 and the Hippo signaling pathway could be closely related to the function of PVT1 in HCC [21]; however, the functions of PVT1 in HCC remain still elusive. In the present study, we sought to explore Fig.…”
Section: Introductionsupporting
confidence: 65%
“…It has been previously shown that PVT1 was highly expressed in HCC compared with non-tumor tissues, and its overexpression predicts recurrence by our group and other groups [21]. We had also surveyed the genetic regulatory network of PVT1 in HCC through a gene microarray and RNAsequecing data mining with bioinformatics method to investigate the potential mechanism of PVT1 in HCC, and found that DLC1 and the Hippo signaling pathway could be closely related to the function of PVT1 in HCC [21]; however, the functions of PVT1 in HCC remain still elusive. In the present study, we sought to explore Fig.…”
Section: Introductionsupporting
confidence: 65%
“…In addition, serum levels of miR-139 were shown to be significantly increased in adrenocortical cancer41. Moreover, the expression of miR139-5p in peripheral blood was significantly higher in prostate cancer patients compared to patients with benign prostatic hyperplasia and healthy controls, and much higher expression of peripheral blood miR-139-5p was detected in prostate cancer patients with more advanced stage and more aggressive tumors42. The current study demonstrated that miR-139-5p was upregulated in primary cancer tissues of patients with recurrence compared to those who did not.…”
Section: Discussionmentioning
confidence: 94%
“…By directly targeting protein-coding genes, miRNAs can inhibit genes that are needed for signaling pathways or drug-induced apoptosis [25]. In recent years, miRNAs have attracted attention in PC [26,27]. Multiple miRNAs are thought to be critical for the control of drug resistance in PC [25].…”
Section: Discussionmentioning
confidence: 99%